2023
DOI: 10.5688/ajpe9035
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Student Research Project Impact Using the Buxton and Hanney Payback Framework

Abstract: Objectives: Determine if evidence of the impact of student quality improvement (QI) and research projects on practice sites and the community can be identified using the Buxton and Hanney Payback Framework (BHPF). Methods: The BHPF was used to identify the broader impact of QI and research projects conducted by the Doctor of Pharmacy Class of 2020. The BHPF includes five domains of community impact: knowledge production, benefits to health or the health sector, benefits to future research, economic benefits, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Incorporating learners into the research process may positively impact learners themselves, mentors, patients, institutions, and the pharmacy profession (Table 1). 1,2,7–11 …”
Section: Benefits Of Learners In Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Incorporating learners into the research process may positively impact learners themselves, mentors, patients, institutions, and the pharmacy profession (Table 1). 1,2,7–11 …”
Section: Benefits Of Learners In Researchmentioning
confidence: 99%
“…Many learners may not feel prepared in research design, data analysis, or medical writing, which can negatively impact motivation to seek or maintain research involvement 6,30–34 . Another barrier, particularly for student pharmacists, can be familiarity with new practice sites, which would require additional training on the electronic health record, policies, formulary, or practice approaches, prior to integration into a project 9 . Furthermore, completion of research or scholarly dissemination may be impacted when learners complete their training or transition to new roles 31–33 .…”
Section: Barriers For Learner Participation In Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown the value of pharmacy students, residents, and fellows conducting research. [6][7][8][9][10][11] However, when pharmacy students, residents, fellows, faculty, or other early career pharmacists do engage in research, it is often their first time, or one of their first times, and they may therefore be unprepared.…”
Section: Introductionmentioning
confidence: 99%
“…Some pharmacy students, residents, or fellows pursue a career in academia where they are typically required to engage in scholarly activities. Studies have shown the value of pharmacy students, residents, and fellows conducting research 6–11 . However, when pharmacy students, residents, fellows, faculty, or other early career pharmacists do engage in research, it is often their first time, or one of their first times, and they may therefore be unprepared.…”
Section: Introductionmentioning
confidence: 99%